Developing multimodal literacy through critical practices : an examlpe from an english for the media university program - Hadjiconstantinou, Stavroulla (My University, 2023)
Among the challenges for language instructors nowadays is to prepare learners to be active- ly and equitably engaged in digitally mediated environments. Drawing on research in Criti- cal Pedagogy that highlights the importance of raising learners’ critical awareness through language (Luke, 2012), this presentation discusses how critical practices of identifying and negotiating the expression of personal opinion in multimodal texts, in an English for the Me- dia context can enhance the development of multimodal literacy. The instructional design discussed in the presentation, is framed by the Critical Thinking (CT) construct of myside bias (Stanovich et al., 2013a) defined in Cognitive Psychology as the inclination to evaluate and generate evidence in a manner biased towards an individual’s own opinions. The design includes the use of authentic multimodal texts such as advertisements and online articles to engage learners in collaborative critical analysis informed by Systemic functional Linguis- tics (Halliday, 1994). The analysis is designed to foreground the social purpose of multimodal texts through explicit discussion of the ways authors use language and other multimodal components such as images to promote or suppress specific views. The design is iterated, assessed and refined as advocated by Design Based Research (DBR) methodology in support of the development of design principles that guide, inform and improve both practice and research in educational contexts. (Collective, 2003). Data analysis indicates that using CT to frame learners’ engagement with multimodal texts can enhance their understanding of the func- tional role of language and other multimodal components in construing meaning (e.g. avoid- ing bias). Furthermore, data shows that iteration of such critical questioning processes may develop habits of mind which seem to enhance learners’ multimodal literacy skills. Finally, it is suggested in this presentation that such or similar practices can be effectively developed or adapted and applied in different language contexts.